Rheumatoid factor interference in immunogenicity assays for human monoclonal antibody therapeutics - Tatarewicz, Suzanna; Miller, Jill M.; Swanson, Steven J.; Moxness, Michael S. (Journal of immunological methods, 2010)
Rheumatoid factors (RFs) are endogenous human antibodies that bind to human gamma globulins. RFs demonstrate preferential binding to aggregated gamma globulins and are involved in the clearing mechanism of immune complexes. Immunoassays designed to measure human anti-human antibodies (HAHA) after administration of monoclonal antibody therapeutics are thus vulnerable to interference from RFs. When using a sensitive electrochemiluminescent (ECL) bridging immunoassay, samples from subjects with rheumatoid arthritis demonstrated much higher baseline reactivity than healthy subjects. Interference was found to be dependent on the aggregation state of the therapeutic antibody that had been conjugated with the detection reagent (ruthenium). Size exclusion high performance liquid chromatography (SE-HPLC) demonstrated that of the total integrated peaks, as little as 0.55% high molecular weight aggregates (> 600 kDa) were sufficient to cause increased reactivity. Stability studies of the ruthenium and biotin conjugated therapeutic antibody indicated that storage time, temperature and buffer formulation were critical in maintaining the integrity of the reagents. Through careful SE-HPLC monitoring we were able to choose appropriate storage and buffer conditions which led to a reduction in the false reactivity rate in therapeutic-naïve serum from a rheumatoid arthritis population.